Analysis Of Factors Affecting Firm Performance In Manufacturing Companies In Indonesia - Wijoyo, Amin; Henny Wirianata (SEAN Institute, 2024)
The study aims to obtain empirical evidence regarding the influence of capital structure, firm size, liquidity, tangibility, leverage, and asset turnover as independent variables on firm performance as a dependent variable. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange during 2019 - 2022. The sample taken was 193 companies. The model used in this study is MicrosoftExcel software and processed using the E-views 10 program